Cross-cultural approach and the characterization of comparative phraseological units - Daliyeva, Madina; Baxronova, Dilrabo (The Lingua Spectrum, 2025)
In recent years, the emergence and widespread application of such conceptual fields as cross-cultural psychology, cross-cultural management, and cross-cultural pedagogy have reaffirmed the relevance of this approach. However, research in this area has yet to address numerous unresolved issues. Furthermore, the term “cross-cultural” remains insufficiently elaborated in scientific and explanatory dictionaries, lacking a precise definition, which underscores the necessity for its further in-depth study. This article aims to define the theoretical foundations of the cross-cultural approach, analyze phraseological expressions and comparative phraseological units, assess their role in scientific discourse, and explore their practical applications.